Experimental Dissection of the Lytic Replication Cycles of Herpes Simplex Viruses in vitro - Ibáñez, Francisco J.; Farías, Mónica A.; Gonzalez-Troncoso, Maria P.; Corrales, Nicolás; Duarte, Luisa F.; Retamal-Díaz, Angello; González, Pablo A. (Frontiers in Microbiology, 2018)
Herpes simplex viruses type 1 and type 2 (HSV-1 and HSV-2) produce lifelong infections and are highly prevalent in the human population. Both viruses elicit numerous clinical manifestations and produce mild-to-severe diseases that affect the skin, eyes and brain, among others. Despite the existence of numerous antivirals against HSV, such as acyclovir and acyclovir-related analogues, virus variants that are resistant to these compounds can be isolated from immunosuppressed individuals. For such isolates, second-line drugs can be used, yet they frequently produce adverse side effects. Furthermore, topical antivirals for treating cutaneous HSV infections usually display poor to moderate efficacy. Hence, better or novel anti-HSV antivirals are needed and details on their mechanisms of action would be insightful for improving their efficacy and identifying specific molecular targets. Here, we review and dissect the lytic replication cycles of herpes simplex viruses, discussing key steps involved in cell infection and the processes that yield new virions. Additionally, we review and discuss rapid, easy-to-perform and simple experimental approaches for studying key steps involved in HSV replication to facilitate the identification of the mechanisms of action of anti-HSV compounds.